Teaching translation and interpreting 2 : insights, aims, visions : papers from the second Language International Conference, Elsinore, Denmark, 4-6 June 1993 - Dollerup, Cay; Lindegaard, Annette (Benjamins translation library, 1994)
Selected papers from this second conference on Translator and Interpreter Training. With contributions from five continents, the articles deal with global challenges, taking into account the role of the translator in societies knit together by one tongue and those in which languages are the repostitories of national cultures, such as India. The main merit of this volume is that it shows how translator training is tackled in the main translator training courses around the world, what requirements are made on the students and what solutions are given. The various approaches provide a wealth of t.